Punitive Populism in Ecuador: At What Stage of the Iter Criminis Is the Principle of Minimum Intervention Infringed? - Silva Guamushig, Bryan Steven (Universidad Hemisferios, 2026)
In the Ecuadorian context, the symbolic instrumentalization of criminal law, driven by social and media pressures, poses a significant risk of infringing the principle of minimum intervention, a cornerstone of the ius puniendi. Only conducts that actually harm or concretely endanger a legally protected interest should be punishable; otherwise, there is a risk of arbitrary expansion of state punitive power. This article analyzes, from the perspective of criminal law dogmatics and through a qualitative-explanatory approach, the stages of the iter criminis, examining the limits of penal intervention at each phase of the criminal path by applying the deductive-analytical method. Using a methodological case study, the paper concludes that punishing internal phases (ideation, deliberation, and resolution) is disproportionate, while sanctioning acts in the intermediate phase (proposition and conspiracy) may lead to illegitimate state intervention that disregards the subsidiary character of criminal law as ultima ratio.